Aeroelastic deformation measurement of Martian airplane for high-altitude flight experiment using stereophotogrammetry. (10th March 2021) - Hiramatsu, Shuichi; Anyoji, Masayuki; Fujita, Koji; Nagai, Hiroki; Oyama, Akira; Kato, Hiroyuki
Abstract: A fixed-wing aircraft called Mars Airplane Balloon Experiment −2 (MABE2) developed by the authors was the subject of high-altitude flight demonstration test in this paper, which can simulate the near-actual environment of a Martian atmospheric flight. Although the flight condition is in the low-Reynolds-number region due to low density at high altitude, the wing suffers from aeroelastic deformation given the relatively high dynamic pressure load in the pull-up phase. Stereophotogrammetry was applied in the 6.5 m × 5.5 m low-speed wind tunnel at the Japan Aerospace Exploration Agency (JAXA), aiming to optically measure MABE2's aeroelastic deformation under dynamic pressure loads equivalent to high-altitude flight test, with the MABE2's reinforced structural strength. The results of the accuracy test indicated that stereophotogrammetry measures aeroelastic deformation at high accuracy of ±0.1 mm around the image center and ±0.3 mm around the edge. A slight deflection of up to 4 mm was observed on the main wing, whereas both the main and tail wings were hardly twisted. Compared with flight-simulation-assumed errors, these deformations are extremely small and have a negligible effect on the high-altitude flight test. The study results confirmed the practicality and efficiency of this optical measurement technique in aeroelastic deformation measurement for a real light aircraft.